What Can Economics Say about Alzheimer’s Disease? - Chandra, Amitabh; Coile, Courtney; Mommaerts, Corina (Journal of Economic Literature, 2023)
Alzheimer's disease (AD) affects one in ten people aged 65 or older and is the most expensive disease in the United States. We describe the central economic questions raised by AD. Although there is overlap with the economics of aging and health, the defining feature of the "economics of Alzheimer's disease" is an emphasis on choice by cognitively impaired patients that affects health and financial well-being, and situations in which dynamic contracts between patients and caregivers are useful but difficult to enforce. A focus on innovation in AD prevention, treatment, and care is also critical given the enormous social cost of AD and present lack of understanding of its causes, which raises questions of optimal resource allocation and alignment of private and social incentives. The enormous scope for economists to contribute to our understanding of AD-related issues including drug development, efficient care delivery, dynamic contracting, long-term care risk, financial decision-making, and the design of public programs for AD suggests a rich research program for many areas of economics.